Kepailitan Perusahaan Pembiayaan: Hak dan Upaya Hukum Kreditur dalam Proses Kepailitan - Zairi Absi, Warmiyana; Cayo, Putri Sari Nilam; Martini, Martini; Aprita, Serlika (Disiplin : Majalah Civitas Akademika Sekolah Tinggi Ilmu Hukum sumpah Pemuda, 2025)
Bankruptcy of a finance company is a condition in which the company is unable to fulfill its obligations to creditors, resulting in a bankruptcy legal process. In the bankruptcy process, creditors have rights that must be considered, including the right to submit bills, attend creditors' meetings, and obtain payments from the liquidation of the bankrupt company's assets. However, problems often arise regarding payment priorities, objections to asset management, and other legal actions that can affect the position of creditors. Therefore, creditors need to understand the legal remedies that can be taken, such as filing objections to bankruptcy decisions, homologation requests, and other legal steps to protect their interests. This article comprehensively discusses the rights and remedies available to creditors in the face of finance company insolvency proceedings, highlighting relevant legal aspects as well as prevailing practices in Indonesia